Existential Psychotherapy: Insights from the Srimad Bhagavad Gita - Kumkaria, Bodhraj; Tiwari, Himalaya (International Journal of Psychosocial Rehabilitation, 2020)
Existential psychotherapy offers a profound framework for addressing the fundamental anxieties of human existence, including death, freedom, isolation, and meaninglessness. Traditionally rooted in Western philosophical thought, this modality has primarily evolved within Euro-American contexts, often overlooking the wealth of psychological insight embedded in Eastern philosophical traditions. The Srimad Bhagavad Gita, a seminal Indian scripture, presents a narrative deeply resonant with existential concerns, offering psychospiritual responses to suffering, crisis, and the quest for self-realization. Through a theoretical and interpretive analysis, this paper explores the integration of existential psychotherapy with insights from the Gita, focusing on themes such as atma jñāna (self-knowledge), karma yoga (action without attachment), and svadharma (personal duty). The existential crisis of Arjuna, as portrayed in the Gita, mirrors the human condition’s confrontation with despair, choice, and moral ambiguity. Krishna’s dialogue provides a therapeutic model that facilitates meaning-making and spiritual transcendence. This paper argues that the Gita’s teachings can complement and deepen existential psychotherapy, particularly within culturally diverse therapeutic contexts. The study contributes to the expanding discourse on culturally integrated psychotherapies and positions the Gita as a valuable psychospiritual resource for clinicians addressing existential anxiety in Indian and global populations.